PEKERJA LANJUT USIA (Studi Di Pasar Dupa Kencana Kota Pekanbaru) - Hafiza Ulfa; Yoskar Kadarisman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The development of various aspects of social, economic and health life is very influential in managing social conditions in society such as the ability of individuals to survive and be able to be in the flow of community development. The role and potential of individuals in society are also assessed from the social adaptability of individuals to be accepted and able to survive in the life of the community. This self potential is not only seen from social factors but involves all factors including age. The potential age is identical to individuals who are in the productive age range such as adolescents and adults, so that in general the view of the public towards age beyond the limits is considered as an inefficient human being and unable to compete economically and socially. But this assumption cannot be denied because there are still many elderly people who are still capable and have the potential to sustain their lives when they are categorized as unproductive. The purpose of this study was to determine the cause of the elderly still working at a young age and the impact that occurred on the elderly who were still working. The research method used is qualitatively by taking 5 subjects of elderly workers. Older workers who work in Pekanbaru City Dupa Kencana Market who are over 60 years old. The results of the study show that the elderly work because of an encouragement or an intrinsic and extrinsic motivation. The intrinsic factor of the elderly works because the desire from within and comes from the hobby while the extrinsic factor of the elderly works because it is a necessity and limitations and activities to get a role in the middle of the environment.Keywords: Worker, Motivation, Elderly